Computerized adaptation of the Placing Test for early detection of both mild cognitive impairment and Alzheimers disease - Vacante, M; Wilcock, G; De Jager, C (2013)
Changes in the hippocampal system have been proposed as a possible marker of incipient Alzheimers disease (AD) at the mild cognitive impairment (MCI) stage. The Placing Test (TPT) evaluates the efficiency of the hippocampal system by measuring the ability to remember associations between images and their locations. Our aim was to validate a novel paper-and-pencil (PnP) version of TPT featuring peoples faces in color (versus the traditional test carried out with black-and-white images) and a computerized Placing test with categories of objects, faces, and animals (versus a version featuring the categories of objects, faces, and shapes). A total of 78 subjects were divided into 2 groups; each group included 20 normal control subjects, 10 subjects with MCI, and 9 with AD. All subjects underwent TPT. The correlation between the two versions of the test was highly significant (r =.770, p <.001), demonstrating that the transfer of the test format from PnP to computer was acceptable. Computerized object and animal subtests had the highest overall sensitivity and specificity for discriminating MCI from AD, while PnP faces in color discriminated controls from MCI best. Although this was a preliminary assessment on a small sample of subjects, the results of our study demonstrated that total scores on both the traditional and computerized versions of the test discriminate all three diagnostic categories, but the subtests had varying discriminatory abilities. © 2013 Taylor and Francis.